Dinamika Reformasi Dan Westernisasi Yang Terjadi Pada Masa Pemerintahan Kerajaan Turki Usmani - Wardana, Andhena Wisnu; Fadil (LPPM IAIN Sorong, 2024)
Since the 17th century the Ottoman Empire began to collapse due to defeat from the West. As a result, the caliphs wanted to reconstruct the government with a Westernized model. Thus, the caliphs wanted to reform and westernize between Turkish culture and Western civilization which culminated in the time of Mustafa Kemal Ataturk. so, what was the dynamic of reform and westernization in the Ottoman Tukri government. This article uses the Normative type of research. Normative research is a type of research whose data is taken from literature studies in the form of books, journals, and so on as well as research results related to the topic of discussion in this study. Then, this article uses he Historical Approach approach, the result and discussion is the development of reforms during the reign of Ottoman Turkey pioneered by Sultan Mahmud II who is famous for the Tanzimat period. then, the flow of leadership was continued by Sultan Abdul Majid thus inaugurating the Gulhane and Humayun Charter. In addition to the Tanzimat era, the renewal of Turkey was carried out by the Young Ottomans and culminated in the leadership of Mustafa Kemal Ataturk. then The implementation of westernization is carried out by three groups, namely Islamism, Westernism,